2019
DOI: 10.21037/acs.2018.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Resource implications of robotic thoracic surgery: what are the wider issues?

Abstract: The benefits of minimally invasive thoracic surgery are well documented when compared to the use of standard thoracotomy. Much controversy exists, however, regarding the resource implications when using robot-assisted thoracic surgery (RATS), especially when compared to video-assisted thoracoscopic surgery (VATS). Much of the costs attributed to a particular approach center around the frequency and severity of the complications that may arise. Little exists in the literature to appropriately compare and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This has also been addressed by Stamenkovic and Slight who concluded that the resource implication benefits of RATS concerning the shorter length of hospital stay, fewer complications, enhanced recovery, and increased uptake of adjuvant treatments contribute towards decreased costs. Currently, there is a commercial expansion of the robot platform market, which may result in a competitive reduction of costs [ 18 ]. This has been further studied in Shanahan et al's comprehensive micro-cost analysis of RATS procedures [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has also been addressed by Stamenkovic and Slight who concluded that the resource implication benefits of RATS concerning the shorter length of hospital stay, fewer complications, enhanced recovery, and increased uptake of adjuvant treatments contribute towards decreased costs. Currently, there is a commercial expansion of the robot platform market, which may result in a competitive reduction of costs [ 18 ]. This has been further studied in Shanahan et al's comprehensive micro-cost analysis of RATS procedures [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the variability was likely due to different cost definitions, it became clear that most of the studies on cost to that date (prior to 2018) were derived from the early experience with robotic lobectomy. In a thoughtful discussion of the wider issues of resource implication of robotics, the guest editor Dr. Stamenkovic points to the close relationship between cost of the robotic technology (i.e., disposables, drapes and staplers), as well as other hospital resources that drive cost, such as operating room time and length of stay (2). Recently, we have critically reviewed our experience with robotic lobectomy to better understand the value of robotics at a high-volume center.…”
mentioning
confidence: 99%